POSHAN's abstract digest on maternal and child nutrition research - Issue 22 - Avula, Rasmi (International Food Policy Research Institute, 2018)
In this issue of Abstract Digest, we have brought together a collection of articles and systematic reviews on multiple aspects of nutrition including stunting, micronutrient supplementation, adolescent nutrition, and policy analysis. Here are some of the highlights.